AUTOMATIC SYSTEM FOR CONTINUOUS MONITORING OF INDOOR AIR QUALITY AND REMOTE DATA TRANSMISSION UNDER SMART_RAD_EN PROJECT - TUNYAGI, Arthur; DICU, Tiberius; SZACSVAI, Kinga; PAPP, Botond; DOBREI, Gabriel; SAINZ, Carlos; TUNYAGI, Arthur (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
In September 2016, the SMART-RAD-EN Project was launched, funded by the Competitiveness Operational Programme 2014-2020 of Romania, to be developed up to the year 2020. The ambitious overall objective is focus on to the concept of "smart city" in terms of intelligent integrated solutions, which it aims to achieve in international premiere, in order to improve public health by increasing indoor environmental quality and optimizing the energy efficiency of housing in five urban areas of Romania. In this study, the current status of the development of the prototype system for continuous monitoring and remote data transmission on radon levels and other household air pollutants (CO2, CO, VOCs and temperature, pressure and humidity sensors) is presented, as an important objective in the frame of the SMART_RAD_EN project. The prototype for intelligent monitoring system was assembled and now is involved in the testing process. Metrology and quality assurance of the prototype system will be carried out within accredited European laboratories and by consulting with the international scientific experts. Remote data transmitted will allow: (1) real time interactive visualization, of the impact of user behavior on indoor air quality; (2) information in case of exceeding threshold levels; (3) to produce estimates of future pollution as a result of the correlation with the meteorological parameters (temperature, pressure and humidity) and user activity. The system, metrological validated, will be implemented in 100 houses with high exposure to radon and other ambient pollutants from the main Romanian urban agllomerations – Cluj-Napoca, Bucuresti, Timisoara, Iasi and Sibiu.